Chronic medium-chain triacylglycerol consumption and endurance performance in trained runners - Misell, L. M.; Lagomarcino, N. D.; Schuster, V.; Kern, M. (The Journal of Sports Medicine and Physical Fitness, 2001)
This study was designed to assess the effects of chronic consumption of medium-chain triacylglycerols (MCT) on endurance running performance. METHODS: Experimental design: participants completed the study in a randomized, cross-over, placebo-controlled, double-blind fashion. Setting: participants were recruited from the general community to participate in this university based study. Participants: twelve trained male endurance runners (30.5+/-5.2 years of age) completed the study. Interventions: participants consumed dietary supplements containing either 56 g of corn oil (LCT) or 60 g of MCT oil daily for 2 weeks. Following each dietary phase, participants completed a maximal treadmill test followed by an endurance treadmill test in which participants ran at 85% VO2max for 30 min proceeded by 75% VO2max until exhaustion. Measures: blood was taken at rest and after 45 min of exercise to assess concentrations of lactate, glucose, b-hydroxybutyrate (b-HBA), free fatty acids (FFA), glycerol and triacylglycerols (TG). Performance was assessed as time to exhaustion. RESULTS: VO2max (72.0+/-8.0 vs 72.4+/- 9.0 ml.kg-1.min-1) and endurance time (99.8+/-23.5 vs 106.5+/-29.4 min) did not differ (p>0.05) between MCT and LCT trials, respectively. No differences (p>0.05) in lactate, glucose, b-HBA, FFA, glycerol or TG were detected between trials. Respiratory exchange ratio (RER) was higher (p<0.05) at 15 min for the MCT trial (0.97+/-0.10) versus the LCT trial (0.90+/-0.20), but was similar between trials at other timepoints. CONCLUSIONS: Results indicate that chronic MCT consumption neither enhances endurance nor significantly alters performance-related metabolism in trained male runners.